Infection of human oligodendroglioma cells by a recombinant measles virus expressing enhanced green fluorescent protein - Plumb, Jonnie (J Neurovirol, 2002)
One of the hallmarks of the human CNS disease subacute sclerosing panencephalitis (SSPE) is a high level of measles virus (MV) infection of oligodendrocytes. It is therefore surprising that there is only one previous report of MV infection of rat oligodendrocytes in culture and no reports of human oligodendrocyte infection in culture. In an attempt to develop a model system to study MV infection of oligodendrocytes, time-lapse confocal microscopy, immunocytochemistry, and electron microscopy (EM) were used to study infection of the human oligodendroglioma cell line, MO3.13. A rat oligodendrocyte cell line, OLN-93, was also studied as a control. MO3.13 cells were shown to be highly susceptible to MV infection and virus budding was observed from the surface of infected MO3.13 cells by EM. Analysis of the infection in real time and by immunocytochemistry revealed that virus spread occurred by cell-to-cell fusion and was also facilitated by virus transport in cell processes. MO3.13 cells were shown to express CD46, a MV receptor, but were negative for the recently discovered MV receptor, signaling leucocyte activation molecule (SLAM). Immunohistochemical studies on SSPE tissue sections demonstrated that CD46 was also expressed on populations of human oligodendrocytes. SLAM expression was not detected on oligodendrocytes. These studies, which are the first to show MV infection of human oligodendrocytes in culture, show that the cells are highly susceptible to MV infection and this model cell line has been used to further our understanding of MV spread in the CNS.